How Content Moderation May Expose Social Media Companies to Greater Defamation Liability - Tanner Bone (Washington University Law Review, 2021)
This Note will explain the critical distinction between “publishers” and “platforms,” why social media entities are currently considered “platforms,” and why the legal system should reevaluate the liability of social media entities based on how they moderate and regulate content. Part I of this Note will discuss the history of the common-law liability of content providers prior to the invention of the internet. It will also explore the history and rationale for enacting Section 230 of the Communications Decency Act (CDA). Part II of this Note will explain the distinction between “publishers” and “platforms” as it relates to defamation liability. Further, it will discuss the rapid growth of social media during the internet age and its impact on communication and the spread of information. It will also discuss the cryptic and often vague algorithmic process that social media companies use to decide which content is visible to users. Part III of this Note will analyze the current liability of social media companies as a “platform” and will discuss the argument that social media is the twenty-first century’s “town square.” Part IV will explain three key pieces of recently proposed legislation that may affect Section 230 of the CDA. Part V of this Note will explain specific changes that social media companies must make to avoid the enhanced defamation liability of moving from the “platform” category to the “publisher” category. Part VI will discuss a few legislative and executive solutions to allow Section 230 of the CDA to reflect the current internet landscape by focusing on pushing social media companies toward transparent content-moderation practices.
Keywords: Social media; Content moderation; Defamation; Communications Decency Act; Section 230; Internet law